Multiple Giant Molluscum Contagiosum Arising on Antiretroviral Therapy: A Visible Marker of Unrecognized Immunological Failure in Advanced HIV Disease - Aulia Yasmin; Endra Yustin Ellistasari; Ammarilis Murastami; Prasetyadi Mawardi (Scientific Journal of Dermatology and Venereology, 2026)
Introduction: Molluscum contagiosum is ordinarily self-limiting, but in profound immunosuppression it becomes extensive, giant and atypical. Published reports almost uniformly describe such lesions as revealing previously undiagnosed HIV. Giant lesions arising in a patient already established on antiretroviral therapy are far less often described, and carry a different and more urgent meaning. Case Presentation: A 39-year-old man presented with one year of enlarging papules and nodules on the eyelids, face, neck, right hand and penis, the largest 3.5 × 2.5 × 1.5 cm, and 18 months of pruritic hyperpigmented limb papules, after 24 months of fixed-dose efavirenz, lamivudine and tenofovir disoproxil. Dermoscopy, Giemsa cytology and histopathology confirmed molluscum contagiosum; the limb eruption was pruritic papular eruption. The CD4 count was 31 cells/µL and the CD8 count 1624 cells/µL, a CD4/CD8 ratio of 0.02. Syphilis serology was non-reactive. Serial excision and enucleation of the facial and cervical lesions, with weekly 90% trichloroacetic acid to the penile lesions, cleared the facial disease by month 3, but the patient deteriorated and died at month 7. No viral load, resistance genotype, cryptococcal antigen or tuberculosis screen was performed. Conclusion: Giant molluscum contagiosum arising after two years of antiretroviral therapy is not simply a marker of advanced HIV disease; it marks therapy that is not working. An audit of this record identified five measurements that were indicated and never obtained. Dermatologists recognizing this eruption should treat the skin and, at the same visit, trigger a viral load and the advanced HIV disease package of care.